Whole-Sellar Stereotactic Radiosurgery for Functioning Pituitary Adenomas. Issue 3 (23rd May 2014) - Lee, Cheng-Chia; Chen, Ching-Jen; Yen, Chun-Po; Xu, Zhiyuan; Schlesinger, David; Fezeu, Francis; Sheehan, Jason P.
Abstract: BACKGROUND: Functioning pituitary adenomas (FPAs) can be difficult to delineate on postoperative magnetic resonance imaging, making them difficult targets for stereotactic radiosurgery (SRS). In such cases, radiation delivery to the entire sella has been utilized as a radiosurgical equivalent of a total hypophysectomy. OBJECTIVE: To evaluate the outcomes of a cohort of patients with FPA who underwent SRS to the whole-sellar region. METHODS: This is a retrospective review of patients who underwent whole-sellar SRS for FPA between 1989 and 2012. Sixty-four patients met the inclusion criteria: they were treated with whole-sellar SRS following surgical resection for persistently elevated hormone levels, and (1) no visible lesions on imaging studies and/or (2) tumor infiltration of dura or adjacent venous sinuses observed at the time of a prior resection. The median radiosurgical volume covering sellar structures was 3.2 mL, with a median margin dose of 25 Gy. RESULTS: The median endocrine follow-up was 41 months; 22 (68.8%) patients with acromegaly, 20 (71.4%) patients with Cushing disease, and 2 (50.0%) patients with prolactinoma achieved endocrine remission. The 2-, 4-, and 6-year actuarial remission rates were 54%, 78%, and 87%, respectively. New-onset neurological deficit was found in 4 (6.3%) patients following treatment. New-onset hypopituitarism was observed in 27 (43.5%) patients, with panhypopituitarism in 2 (3.2%). Higher margin/maximum dose were significantly associated with a higher remission rate and development of post-SRS hypopituitarism. CONCLUSION: Whole-sellar SRS for invasive or imaging-negative FPA following failed resection can offer reasonable rates of endocrine remission. Hypopituitarism following whole-sellar SRS is the most common complication.